An Improved Bilinear Interpolation Algorithm of Converting Standard-Definition Television Images to High-Definition Television Images - Lu Jing; Si Xiong; Wu Shihong (ICIE 2009 : 2009 WASE International Conference on Information Engineering :10-11 July 2009, Taiyuan, Shanxi, China, 2009)
It's very hard to guarantee high image quality whenconverting standard-definition television (SDTV) images tohigh-definition television (HDTV) images because of the greatdifference of image resolution between them. Moreover, thechange in pixel shape from rectangular to square makes thetraditional image zooming methods impossible to do theconversion. Based on this reason, we propose an ImprovedBilinear Interpolation Algorithm: using the CenterCoordinates of Pixels to do bilinear interpolation (IBIACCP).This method can correct the color values of HDTV images bycorrecting the pixels' x and y coordinates since a pixel's colorvalue is a function of its x and y coordinates in interpolationalgorithms. Considering the huge enlarging multiples, we dosharpening treatment to the HDTV images after theinterpolation. Experiments show that IBIACCP can greatlyimprove the quality of HDTV images comparing withtraditional bilinear interpolation algorithm.